2019
DOI: 10.1002/ente.201901163
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium Sulfide@Sulfur Composites as High‐Performance Cathode for Advanced Lithium–Sulfur Batteries

Abstract: Lithium–sulfur batteries have attracted a lot of attention in recent years due to their high theoretical capacity of 1675 mAh g−1 and low cost. However, the shuttle effect caused by the dissolution and migration of polysulfides and the destruction of cathode particles due to volume expansion during lithiation are key issues for their practical application. Herein, a one‐pot hydrothermal preparation of a VS2@S composite as a cathode for lithium–sulfur batteries is reported. The VS2@S composite shows uniform and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Sulfur hosts that function as alternatives to carbons, and encompass both good electronic and ionic conductivity can address these difficulties, such as transition metal sulfides (M x S y , M = V, Ti, Fe, Ni, Mo, etc.). [ 22–25 ] Some of these materials not only display excellent electronic conductivity (comparable to, or better than carbons), but also good Li‐ion diffusion properties and chemical stability, and interfacial compatibility with sulfur/thiophosphate materials. [ 26,27 ] They can also be involved in electrochemical reactions with lithium based on a dual insertion/conversion mechanism and thus contribute additional capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfur hosts that function as alternatives to carbons, and encompass both good electronic and ionic conductivity can address these difficulties, such as transition metal sulfides (M x S y , M = V, Ti, Fe, Ni, Mo, etc.). [ 22–25 ] Some of these materials not only display excellent electronic conductivity (comparable to, or better than carbons), but also good Li‐ion diffusion properties and chemical stability, and interfacial compatibility with sulfur/thiophosphate materials. [ 26,27 ] They can also be involved in electrochemical reactions with lithium based on a dual insertion/conversion mechanism and thus contribute additional capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the VS 2 /S cathode (1.68 mg cm −2 ) shows a discharge capacity of ∼341.1 at 3 C as well as a cycle decay of ∼0.16% during 200 cycles (0.2 C). Chen et al 75 demonstrated that in the VS 2 @S host, the porous structure accommodates the volumetric expansion that occurred during S lithiation, and the VS 2 shows a strong adsorption capability to LiPSs. Therefore, the VS 2 @S cathode presents a capacity of 413 mAh g −1 after 200 cycles at 1 C. Guo et al 59 found that the defect-abundant VS 2 with versatile pores contributes to suppressing the LiPSs shuttling via chemical anchoring.…”
Section: Two-step Deposition Methodmentioning
confidence: 99%
“…Wu et al 4 used a facile hydrothermal method to prepare VS 2 nanoflowers (NFs) comprised of aligned ultrathin nanosheets, where 1.16 mg/ cm 2 S (47 wt %) is supported on the surface of the VS 2 NFs host. Chen et al 75 developed VS 2 nanoparticles self-assembled microflowers that load 75 wt % S, (Figure 14B). Cheng et al 14 synthesized a Co-doped VN (Co-VN) microflower hierarchical structure with a 5% Co/V ratio as a substrate material, where 4.42 mg/cm 2 S are supported on the surface of the Co-VN host (Figure 14C).…”
Section: Strategies For Increasing Effective Areal S Loadingmentioning
confidence: 99%
“…[154] Copyright 2020, Elsevier BV. f) Plot of binding energies of Li 2 S x (x = 1, 2, 4, 6 and 8) on CoS 2 (200) and NiS 2 (200) planes. Reproduced with permission.…”
Section: Metal Dichalcogenidementioning
confidence: 99%